Molecular Detection and Isolation of Fowl Adneovirus Serotype 11 from Chicken Flocks in Kerala - Sandhiya, Kirouchendraji; Rajasekhar, Ravindran; Ravishankar, Chintu; Kanjirakkuzhiyil, Sumod; Sarma , Suprativ; P, Vishnu; S, Abhijith; N, Madhanraj (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Fowl adenovirus (FAdV) is prevalent across the globe, leading to significant economic setbacks in poultry sector. FAdV infection predominantly affect broilers, also there have been sporadic accounts involving commercial layers. The present research work was attributed to molecular detection and isolation of FAdV from poultry flocks in Kerala. Tissue samples of liver, kidney, heart were collected from flocks showing symptoms and lesions suspecting for FAdV infection. DNA was extracted from these clinical specimens by Phenol-chloroform method. PCR for the detection of FAdV targeting hypervariable region of L1 loop of hexon gene was carried out. Out of 50 samples tested, 5 broiler flocks of age 3 weeks were found positive for FAdV, based on the amplification of partial hexon gene. The hexon gene sequence of these isolates showed that the FAdVs isolates were belonging to serotype 11 of FAdVD genotype group on BLAST analysis. Virus isolation was performed in specific pathogen free (SPF) eggs and in chicken embryo fibroblast (CEF). The inoculated embryos showed symptoms of curling and dwarfing. Haemorrhages and necrosis were observed in liver of the infected embryos. The infected cells in CEF showed cytopathic effects, characterized by swelling, rounding, and detachment. Further, the isolate in the embryonated chicken eggs and CEF cell culture were confirmed by PCR.